An Implementation of Time Line Events Visualization Tool Using Forensic Digger Algorithm - Khatik, Priyanka; Choudhary, Preeti (International Journal of Computer Sciences and Engineering, 2014)
Introduction should lead the reader to the importance of the study; tie-up published literature with the aims of the study and clearly states the rationale behind the investigation. It should state the purpose and summarize the rationale for the study and gives a concise background. Use references to provide the most salient background rather than an exhaustive review. The last sentence should concisely state your purpose for carrying out the study.